Shock-absorbing energy-absorbing recyclable material and preparation method thereof

CN122978632APending Publication Date: 2026-10-27ANHUI XUANKE LANYU NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611210346.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种减震吸能可回收材料及制备方法,本发明制备的减震吸能可回收材料能够实现阻尼性能、服役稳定性,该发明以乙烯基封端硼化硅氧烷低聚物与巯基化多孔硅酮微球作为功能组分,借助硫醇-烯点击反应使阻尼相以共价键形式锚定于马来酸酐接枝SEBS基体网络,从分子尺度解决传统物理共混体系中极性硼硅组分与非极性弹性体相容性差、小分子助剂易迁移析出的固有难题,有效抑制了材料长期服役过程中的表面出油、发粘及硼化物析出腐蚀现象,热老化后性能衰减幅度小,不会对接触的精密器件、织物造成二次污染,显著延长了材料使用寿命并拓宽了场景适配范围

Benefits of technology

[0025]1.本发明制备的减震吸能可回收材料能够实现阻尼性能、服役稳定性,该发明以乙烯基封端硼化硅氧烷低聚物与巯基化多孔硅酮微球作为功能组分,借助硫醇-烯点击反应使阻尼相以共价键形式锚定于马来酸酐接枝SEBS基体网络,从分子尺度解决传统物理共混体系中极性硼硅组分与非极性弹性体相容性差、小分子助剂易迁移析出的固有难题,有效抑制了材料长期服役过程中的表面出油、发粘及硼化物析出腐蚀现象,热老化后性能衰减幅度小,不会对接触的精密器件、织物造成二次污染,显著延长了材料使用寿命并拓宽了场景适配范围。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a shock-absorbing energy-absorbing recyclable material and a preparation method thereof, and belongs to the technical field of shock-absorbing energy-absorbing materials. The shock-absorbing energy-absorbing recyclable material prepared by the application can realize damping performance and service stability. The application takes vinyl-terminated borosiloxane oligomers and mercapto porous silicone microspheres as functional components, and covalently anchors the damping phase in the maleic anhydride grafted SEBS matrix network by means of thiol-ene click reaction, so as to solve the inherent problems of poor compatibility between the polar borosilicon component and the non-polar elastomer in the traditional physical blending system, easy migration and precipitation of small molecule additives, effectively inhibit the surface oiling, stickiness and boride precipitation corrosion phenomena in the long-term service process of the material, the performance attenuation amplitude is small after heat aging, the material will not cause secondary pollution to the contacted precision devices and fabrics, the service life of the material is significantly prolonged, and the scene adaptation range is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of shock-absorbing and energy-absorbing materials technology, specifically a shock-absorbing and energy-absorbing recyclable material and its preparation method. Background Technology

[0002] Vibration damping materials are a class of functional materials that dissipate vibration and impact energy through their viscoelastic deformation. They are widely used in many fields such as vibration reduction in rail transit, seismic isolation of buildings and bridges, vibration damping of precision instruments, cushioning of sports protective gear, midsoles of footwear, and military protective equipment. They play a crucial role in improving the operational accuracy, structural safety and reliability, and user comfort of equipment. With the rapid development of high-end manufacturing, new energy, and consumption upgrades, the industry's performance requirements for damping materials are constantly increasing. In addition to high-efficiency vibration damping and energy absorption capabilities, they also need to possess comprehensive properties such as wide-temperature range service stability, no exudation during long-term use, and green recyclability.

[0003] Thermoplastic styrene-based elastomers (SEBS) have become one of the mainstream matrix materials in the current civilian and industrial damping fields due to their excellent weather resistance, processing fluidity, heat recyclability, and cost advantages. However, the intrinsic damping performance of pure SEBS is limited, with a low loss factor and a narrow effective damping temperature range. It usually needs to be modified and improved by blending damping additives and inorganic fillers. Among them, boron-modified siloxane systems can achieve efficient molecular-level energy dissipation due to the reversible fracture-recombination characteristics of BO dynamic coordination bonds, which is an important research direction for high-damping functional phases. Porous silicone microspheres can improve damping performance and mechanical support through interfacial friction and chain segment confinement effects, and are often used as functional fillers for the modification of damping materials.

[0004] In summary, existing SEBS-based damping and energy-absorbing materials generally suffer from technical bottlenecks such as poor compatibility between the functional phase and the matrix, easy migration and precipitation of additives, narrow damping temperature range, and poor recyclability. They are unable to simultaneously meet the multiple performance requirements of high-end applications for high damping, wide temperature range, long life, and recyclability. There is an urgent need to develop new modification technologies to solve these problems. Summary of the Invention

[0005] The purpose of this invention is to provide a shock-absorbing and energy-absorbing recyclable material and its preparation method. The shock-absorbing and energy-absorbing recyclable material prepared by this invention can achieve damping performance and service stability. This invention uses vinyl-terminated borosilicate oligomers and mercapto-modified porous silicone microspheres as functional components. Through the thiol-ene click reaction, the damping phase is covalently anchored to the maleic anhydride-grafted SEBS matrix network. This solves the inherent problems of poor compatibility between polar borosilicate components and non-polar elastomers and easy migration and precipitation of small molecule additives in traditional physical blending systems at the molecular scale. It effectively inhibits surface oiling, stickiness and boride precipitation corrosion during long-term service of the material. The performance degradation after thermal aging is small and will not cause secondary pollution to precision devices and fabrics in contact with it. It significantly extends the service life of the material and broadens the scope of application.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] A method for preparing a shock-absorbing and energy-absorbing recyclable material includes the following steps:

[0008] Step 1: Using vinyl hydroxyl silicone oil as a reaction precursor, the BO dynamic coordination bond is introduced into the main chain of the siloxane molecule through the dehydration condensation reaction of silanol and boric acid to obtain ethylene-terminated siloxane oligomers.

[0009] Step 2: Using an oil-in-water emulsion sol-gel process, mercaptopropyltrimethoxysilane and tetraethyl orthosilicate are used as co-hydrolysis precursors. After the hydrolysis and condensation reaction, while forming a three-dimensional framework of silicone microspheres, thiol functional groups are uniformly introduced into the surface of the microspheres and the framework structure to obtain thiolized silicone microspheres.

[0010] Step 3: By fully penetrating the naphthenic oil molecules into the intersegments of the maleic anhydride-grafted SEBS rubber phase, the matrix is ​​modified by oil filling. Then, through low-speed physical blending, the ethylene-terminated siloxane oligomer, mercaptosilicone microspheres, thermal initiator, and UV absorber UV-327 are uniformly dispersed in the oil-filled matrix to obtain a mixture. This mixture is then extruded by a twin-screw extruder and pelletized to obtain a shock-absorbing and energy-absorbing recyclable material.

[0011] Furthermore, the specific preparation steps for ethylene-terminated siloxane oligomers are as follows:

[0012] Vinyl hydroxy silicone oil is added to a sealed reactor equipped with a stirrer, a reflux condenser, and a nitrogen port. Nitrogen is purged for 5 minutes to completely remove air from the reactor. The mixture is stirred at 120-130 rpm for 20-30 minutes and heated to 130-140°C. Boric acid is then added, and the mixture is kept at 130-140°C for 3-5 hours to allow the hydroxyl groups and boric acid to undergo dehydration condensation and form BO dynamic coordination bonds. After the reaction is complete, a vacuum system is activated to remove the generated small molecule water and unreacted free boric acid at -0.095 MPa for 1-2 hours. The mixture is then cooled to room temperature and discharged to obtain a colorless and transparent high viscoelastic material, which is the ethylene-terminated siloxane oligomer.

[0013] Furthermore, the mass ratio of vinyl hydroxy silicone oil to boric acid is 90-100:3-5.

[0014] Furthermore, the specific preparation steps of the thiolized silicone microspheres are as follows:

[0015] Sodium dodecyl sulfate, anhydrous ethanol, and deionized water were added to a reaction vessel and stirred for 20-30 min at 20-25℃ and 400-500 r / min to obtain an aqueous emulsion. KH-580, tetraethyl orthosilicate, and liquid paraffin were added to the reaction vessel and stirred for 20-30 min at 20-25℃ and 400-500 r / min to obtain an oil phase reaction solution. The oil phase was slowly added dropwise to the aqueous phase and stirred for 20-30 min at 30-35℃ and 400-500 r / min. Ammonia was added dropwise to adjust the pH of the system to 9-10, and the reaction was continued at a constant temperature with stirring for 6-8 h. The mixture was centrifuged at 8000-9000 r / min for 3-5 min and washed 2-4 times with anhydrous ethanol and deionized water to remove unreacted monomers on the surface. The filter cake was placed in a vacuum drying oven at 60-80℃ and dried for 12-14 h to obtain mercapto-modified silicone microspheres.

[0016] Furthermore, the ratio of sodium dodecyl sulfate, anhydrous ethanol, and deionized water is 0.5-0.8 g: 10-12 mL: 89-92 mL.

[0017] Furthermore, the ratio of KH-580, tetraethyl orthosilicate, and liquid paraffin is 60-70g: 30-40g: 10-12g.

[0018] Furthermore, the specific preparation steps for the mixture are as follows:

[0019] Maleic anhydride-grafted SEBS and naphthenic oil are added to a high-speed mixer and stirred for 20-30 minutes at 20-25°C and 400-500 r / min to obtain an oil-filled matrix. The oil-filled matrix, ethylene-terminated siloxane oligomer, mercaptolated silicone microspheres, dicumyl peroxide, antioxidant 1010, and ultraviolet absorber UV-327 are added to the high-speed mixer and stirred for another 20-30 minutes to obtain a mixture.

[0020] Furthermore, the mass ratio of maleic anhydride grafted SEBS to naphthenic oil is 3-5:2-4.

[0021] Furthermore, the ratio of the amount of oil-extended matrix, ethylene-terminated siloxane oligomer, mercaptolated silicone microspheres, dicumyl peroxide, antioxidant 1010 and ultraviolet absorber UV-327 is 60-70g / 15-25g: 8-15g: 0.1-0.5g: 0.2-0.4g: 0.2-0.4g.

[0022] Furthermore, the specific preparation steps for the shock-absorbing and energy-absorbing recyclable material are as follows:

[0023] The mixture is added to a twin-screw extruder and melt-blended at 350-400 r / min, a feeding rate of 15-17 kg / h, a nitrogen atmosphere, and 150-160°C. The mixture is then pelletized to obtain a shock-absorbing and energy-absorbing recyclable material.

[0024] The beneficial effects of this invention are:

[0025] 1. The shock-absorbing and energy-absorbing recyclable material prepared by this invention can achieve damping performance and service stability. This invention uses vinyl-terminated borosilicate oligomers and mercapto-modified porous silicone microspheres as functional components. The damping phase is anchored to the maleic anhydride-grafted SEBS matrix network in the form of covalent bonds by means of thiol-ene click reaction. It solves the inherent problems of poor compatibility between polar borosilicate components and non-polar elastomers and easy migration and precipitation of small molecule additives in traditional physical blending systems at the molecular scale. It effectively inhibits surface oiling, stickiness and boride precipitation corrosion during long-term service of the material. The performance degradation after thermal aging is small and will not cause secondary pollution to precision devices and fabrics in contact with it. It significantly extends the service life of the material and broadens the scope of application.

[0026] 2. In terms of damping mechanism, this invention constructs a molecular-level BO dynamic bond and a multi-level energy dissipation network that can reversibly dissipate energy. The BO coordination bonds in the borosiloxane chain segment can undergo reversible breakage and recombination under external force, efficiently dissipating impact and vibration energy. The porous silicone microspheres further expand the damping response range through friction and chain segment confinement motion effects. The two work together to enable the material to maintain a stable high loss factor over a wide temperature range, overcoming the common bottlenecks in the industry such as narrow effective damping temperature range, sudden drop in damping at low temperature hardening, and insufficient support at high temperature softening of traditional damping materials.

[0027] 3. In terms of recyclability, both the BO dynamic coordination bonds and the sulfide covalent bonds in the system have thermal reversibility, giving the material high-performance recycling capability. After multiple heat processing cycles, the polymer network can be rebuilt in situ without phase separation or damping phase agglomeration. The retention rate of damping and mechanical properties is much higher than that of conventional physical blend thermoplastic damping materials, achieving the design goal of green recyclability. In addition, the hardness of the material can be flexibly adjusted by the component ratio, combining a soft and comfortable touch with excellent energy absorption and shock absorption performance. It can be widely adapted to diverse application scenarios such as sports protective gear, shoe cushioning, vibration isolation of building bridges, vibration reduction of precision instruments, and military protection. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1: A method for preparing a shock-absorbing and energy-absorbing recyclable material, comprising the following steps:

[0030] S1: Add 90g of vinyl hydroxyl silicone oil to a sealed reactor equipped with a stirrer, a reflux condenser, and a nitrogen port. Purge with nitrogen for 5 minutes to completely remove air from the reactor. Stir at 120r / min for 20 minutes, heat to 130℃, then add 3g of boric acid. Keep the reactor at 130℃ for 3 hours to allow the hydroxyl groups and boric acid to undergo dehydration condensation and form BO dynamic coordination bonds. After the reaction is complete, turn on the vacuum system and remove the generated small molecule water and unreacted free boric acid at -0.095MPa for 1 hour. After cooling to room temperature, discharge the material to obtain a colorless and transparent high viscoelastic, which is the ethylene-terminated siloxane oligomer.

[0031] S2: Add 0.5g sodium dodecyl sulfate, 10mL anhydrous ethanol, and 89mL deionized water to a reaction vessel and stir for 20min at 20℃ and 400r / min to obtain an aqueous emulsion. Add 60g KH-580, 30g tetraethyl orthosilicate, and 10g liquid paraffin to a reaction vessel and stir for 20min at 20℃ and 400r / min to obtain an oil phase reaction solution. Slowly add the oil phase to the aqueous phase and stir for 20min at 30℃ and 400r / min. Add ammonia to adjust the pH of the system to 9 and continue stirring at a constant temperature for 6h. Centrifuge at 8000r / min for 3min and wash twice with anhydrous ethanol and deionized water to remove unreacted monomers on the surface. Place the filter cake in a vacuum drying oven at 60℃ for 12h to obtain mercapto-modified silicone microspheres.

[0032] S3: Add 30g of maleic anhydride-grafted SEBS and 20g of naphthenic oil to a high-speed mixer and stir for 20min at 20℃ and 400r / min to obtain an oil-filled matrix; add 60g of the oil-filled matrix, 15g of ethylene-terminated siloxane oligomer, 8g of mercaptolated silicone microspheres, 0.1g of dicumyl peroxide, 0.2g of antioxidant 1010 and 0.2g of UV absorber UV-327 to the high-speed mixer and continue stirring for 20min to obtain a mixture.

[0033] S4: Add the mixture to a twin-screw extruder, melt-blend at 350 r / min, feed rate 15 kg / h, nitrogen atmosphere and 150°C, pelletize, and obtain shock-absorbing and energy-absorbing recyclable material.

[0034] Example 2: A method for preparing a shock-absorbing and energy-absorbing recyclable material, comprising the following steps:

[0035] S1: Add 95g of vinyl hydroxyl silicone oil to a sealed reactor equipped with a stirrer, a reflux condenser, and a nitrogen port. Purge with nitrogen for 5 minutes to completely remove air from the reactor. Stir at 125r / min for 25 minutes, heat to 135℃, then add 4g of boric acid. Keep the reactor at 135℃ for 4 hours to allow the hydroxyl groups and boric acid to undergo dehydration condensation and form BO dynamic coordination bonds. After the reaction is complete, turn on the vacuum system and remove the generated small molecule water and unreacted free boric acid at -0.095MPa for 1.5 hours. After cooling to room temperature, discharge the material to obtain a colorless and transparent high viscoelastic, which is the ethylene-terminated siloxane oligomer.

[0036] S2: Add 0.65g sodium dodecyl sulfate, 11mL anhydrous ethanol, and 90.5mL deionized water to a reaction vessel and stir for 25min at 22.5℃ and 450r / min to obtain an aqueous emulsion. Add 65g KH-580, 35g tetraethyl orthosilicate, and 11g liquid paraffin to a reaction vessel and stir for 25min at 22.5℃ and 450r / min to obtain an oil phase reaction solution. Slowly add the oil phase to the aqueous phase and stir for 25min at 32.5℃ and 450r / min. Add ammonia water to adjust the pH of the system to 9.5 and continue to stir at a constant temperature for 7h. Centrifuge at 8500r / min for 4min and wash three times with anhydrous ethanol and deionized water to remove unreacted monomers on the surface. Place the filter cake in a vacuum drying oven at 70℃ for 13h to obtain mercapto-modified silicone microspheres.

[0037] S3: Add 40g of maleic anhydride-grafted SEBS and 30g of naphthenic oil to a high-speed mixer and stir for 25min at 22.5℃ and 450r / min to obtain an oil-filled matrix; add 65g of the oil-filled matrix, 20g of ethylene-terminated siloxane oligomer, 11.5g of mercaptolated silicone microspheres, 0.3g of dicumyl peroxide, 0.3g of antioxidant 1010 and 0.3g of UV absorber UV-327 to the high-speed mixer and continue stirring for 25min to obtain a mixture.

[0038] S4: Add the mixture to a twin-screw extruder, melt-blend at 375 r / min, feed rate 16 kg / h, nitrogen atmosphere and 155°C, pelletize, and obtain shock-absorbing and energy-absorbing recyclable material.

[0039] Example 3: A method for preparing a shock-absorbing and energy-absorbing recyclable material, comprising the following steps:

[0040] S1: Add 100g of vinyl hydroxyl silicone oil to a sealed reactor equipped with a stirrer, a reflux condenser, and a nitrogen port. Purge with nitrogen for 5 minutes to completely remove air from the reactor. Stir at 130r / min for 30 minutes, heat to 140℃, then add 5g of boric acid. Keep the reactor at 140℃ for 5 hours to allow the hydroxyl groups and boric acid to undergo dehydration condensation and form BO dynamic coordination bonds. After the reaction is complete, turn on the vacuum system and remove the generated small molecule water and unreacted free boric acid at -0.095MPa for 2 hours. After cooling to room temperature, discharge the material to obtain a colorless and transparent high viscoelastic, which is the ethylene-terminated siloxane oligomer.

[0041] S2: Add 0.8g sodium dodecyl sulfate, 12mL anhydrous ethanol, and 92mL deionized water to a reaction vessel and stir for 30min at 25℃ and 500r / min to obtain an aqueous emulsion. Add 70g KH-580, 40g tetraethyl orthosilicate, and 12g liquid paraffin to the reaction vessel and stir for 30min at 25℃ and 500r / min to obtain an oil phase reaction solution. Slowly add the oil phase to the aqueous phase and stir for 30min at 35℃ and 500r / min. Add ammonia to adjust the pH of the system to 10 and continue stirring at a constant temperature for 8h. Centrifuge at 9000r / min for 5min and wash four times with anhydrous ethanol and deionized water to remove unreacted monomers on the surface. Place the filter cake in a vacuum drying oven at 80℃ for 14h to obtain mercapto-modified silicone microspheres.

[0042] S3: Add 50g of maleic anhydride-grafted SEBS and 40g of naphthenic oil to a high-speed mixer and stir for 30min at 25℃ and 500r / min to obtain an oil-filled matrix; add 70g of the oil-filled matrix, 25g of ethylene-terminated siloxane oligomer, 15g of mercaptolated silicone microspheres, 0.5g of dicumyl peroxide, 0.4g of antioxidant 1010 and 0.4g of UV absorber UV-327 to the high-speed mixer and continue stirring for 30min to obtain a mixture.

[0043] S4: Add the mixture to a twin-screw extruder, melt-blend at 400 r / min, feed rate 17 kg / h, nitrogen atmosphere and 160°C, pelletize, and obtain shock-absorbing and energy-absorbing recyclable material.

[0044] Comparative Example 1: Based on Example 3, the ethylene-terminated siloxane oligomer prepared in step S1 was replaced with the raw material vinyl hydroxyl silicone oil.

[0045] Comparative Example 2: Based on Example 3, the mercapto-silicone microspheres in step S3 were removed.

[0046] The shock-absorbing and energy-absorbing recyclable materials prepared in Examples 1-3 were subjected to hot pressing and sheet testing to measure hardness, loss factor, and temperature range. The results are shown in Table 1.

[0047] Hardness reference standard: GB / T 531.1-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber.

[0048] Loss factor test conditions: 0-80℃, 5℃ / min, frequency 1Hz, dynamic force 4N, maximum amplitude 50 micrometers.

[0049] Table 1

[0050] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 hardness 62±3 65±3 67±3 56±3 61±3 Loss factor 1.32 1.30 1.27 0.82 1.08 Temperature range(℃) 10-54 9-56 8-57 14-46 12-51

[0051] As can be seen from Table 1, the core defect of this group in Comparative Example 1 is the loss of the core damping functional unit, the BO dynamic coordination bond introduced by the borylation modification. The specific defects are as follows:

[0052] The reversible breaking and recombination of BO dynamic bonds is the core molecular-level energy dissipation mechanism in this scheme. Without it, the system can only dissipate energy through physical friction of siloxane segments and interfacial friction of silicone microspheres, resulting in a significant decrease in the loss factor and a substantial reduction in the absorption efficiency of shocks and vibrations, making it impossible to achieve efficient vibration damping and energy absorption. The dynamic reversibility of BO bonds is key to maintaining stable damping of the material over a wide temperature range: at low temperatures, bond recombination can alleviate segment freezing, and at high temperatures, bond action can inhibit network softening. Without it, the material is prone to hardening and a sharp drop in damping at low temperatures, and prone to rheological changes and loss of support at high temperatures, resulting in a significant narrowing of the effective damping temperature range and a severe decrease in its adaptability to various scenarios.

[0053] In Comparative Example 2, the removal of the thiolized silicone microspheres retained the BO dynamic bond core damping mechanism, but lost the synergistic effect of the silicone microspheres. The specific disadvantages are as follows:

[0054] Porous silicone microspheres can extend the damping response range through chain segment confinement and interfacial friction effects: limiting excessive freezing of chain segments at low temperatures and constraining excessive chain segment movement at high temperatures. Without these effects, the material's damping temperature range narrows, damping decreases more rapidly at low temperatures, and softening accelerates at high temperatures, thus negating its advantage of wide-temperature-range stable damping.

[0055] Without the multi-level synergistic dissipation of the microspheres and borosilicate phase, relying solely on the single-level energy dissipation of the BO dynamic bonds reduces the overall loss factor, particularly weakening the absorption effect for high-frequency, small-amplitude vibrations, resulting in insufficient comprehensive damping and energy absorption. Thiol-modified silicone microspheres, as rigid functional fillers, can provide physical reinforcement and increase the system modulus. Removing them reduces the material's hardness and resistance to deformation, making it prone to creep under load and unsuitable for applications requiring structural support. Thiol-modified microspheres can covalently bond with the matrix through thiol-olefin reactions, acting as additional crosslinking nodes. Their absence reduces the crosslinking point density, decreases the integrity of polymer network reconstruction after multiple thermal processing cycles, and reduces the retention rate of damping and mechanical properties after recycling and reuse.

[0056] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a shock-absorbing and energy-absorbing recyclable material, characterized in that, Includes the following steps: Step 1: Using vinyl hydroxyl silicone oil as a reaction precursor, the BO dynamic coordination bond is introduced into the main chain of the siloxane molecule through the dehydration condensation reaction of silanol and boric acid to obtain ethylene-terminated siloxane oligomers. Step 2: Using an oil-in-water emulsion sol-gel process, mercaptopropyltrimethoxysilane and tetraethyl orthosilicate are used as co-hydrolysis precursors. After the hydrolysis and condensation reaction, while forming a three-dimensional framework of silicone microspheres, thiol functional groups are uniformly introduced into the surface of the microspheres and the framework structure to obtain thiolized silicone microspheres. Step 3: The matrix is ​​modified by fully penetrating the intersegments of the maleic anhydride-grafted SEBS rubber phase chain through naphthenic oil molecules. Then, through low-speed physical blending, the ethylene-terminated siloxane oligomer, mercaptosilicone microspheres, thermal initiator and UV absorber UV-327 are uniformly dispersed in the oil-filled matrix to obtain a mixture. The mixture is then extruded by twin screw extrusion and pelletized to obtain a shock-absorbing and energy-absorbing recyclable material.

2. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 1, characterized in that, The specific preparation steps for the ethylene-terminated siloxane oligomer are as follows: Vinyl hydroxy silicone oil is added to a sealed reactor equipped with a stirrer, a reflux condenser, and a nitrogen port. Nitrogen is purged for 5 minutes to completely remove air from the reactor. The mixture is stirred at 120-130 rpm for 20-30 minutes and heated to 130-140°C. Boric acid is then added, and the mixture is kept at 130-140°C for 3-5 hours to allow the hydroxyl groups and boric acid to undergo dehydration condensation and form BO dynamic coordination bonds. After the reaction is complete, a vacuum system is activated to remove the generated small molecule water and unreacted free boric acid at -0.095 MPa for 1-2 hours. The mixture is then cooled to room temperature and discharged to obtain a colorless and transparent high viscoelastic material, which is the ethylene-terminated siloxane oligomer.

3. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 2, characterized in that, The mass ratio of the vinyl hydroxy silicone oil to boric acid is 90-100:3-5.

4. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 1, characterized in that, The specific preparation steps of the mercapto-silicone microspheres are as follows: Sodium dodecyl sulfate, anhydrous ethanol, and deionized water were added to a reaction vessel and stirred for 20-30 min at 20-25℃ and 400-500 r / min to obtain an aqueous emulsion. KH-580, tetraethyl orthosilicate, and liquid paraffin were added to the reaction vessel and stirred for 20-30 min at 20-25℃ and 400-500 r / min to obtain an oil phase reaction solution. The oil phase was slowly added dropwise to the aqueous phase and stirred for 20-30 min at 30-35℃ and 400-500 r / min. Ammonia was added dropwise to adjust the pH of the system to 9-10, and the reaction was continued at a constant temperature with stirring for 6-8 h. The mixture was centrifuged at 8000-9000 r / min for 3-5 min and washed 2-4 times with anhydrous ethanol and deionized water to remove unreacted monomers on the surface. The filter cake was placed in a vacuum drying oven at 60-80℃ and dried for 12-14 h to obtain mercapto-modified silicone microspheres.

5. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 4, characterized in that, The ratio of sodium dodecyl sulfate, anhydrous ethanol, and deionized water is 0.5-0.8g: 10-12mL: 89-92mL.

6. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 4, characterized in that, The ratio of KH-580, tetraethyl orthosilicate, and liquid paraffin is 60-70g: 30-40g: 10-12g.

7. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 1, characterized in that, The specific preparation steps for the mixture are as follows: Maleic anhydride-grafted SEBS and naphthenic oil are added to a high-speed mixer and stirred for 20-30 minutes at 20-25°C and 400-500 r / min to obtain an oil-filled matrix. The oil-filled matrix, ethylene-terminated siloxane oligomer, mercaptolated silicone microspheres, dicumyl peroxide, antioxidant 1010, and ultraviolet absorber UV-327 are added to the high-speed mixer and stirred for another 20-30 minutes to obtain a mixture.

8. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 7, characterized in that, The mass ratio of maleic anhydride-grafted SEBS to naphthenic oil is 3-5:2-4; the dosage ratio of the oil-extended matrix, ethylene-terminated siloxane oligomer, mercaptolated silicone microspheres, dicumyl peroxide, antioxidant 1010, and ultraviolet absorber UV-327 is 60-70g / 15-25g: 8-15g: 0.1-0.5g: 0.2-0.4g: 0.2-0.4g.

9. The method for preparing a shock-absorbing and energy-absorbing recyclable material according to claim 1, characterized in that, The specific preparation steps of the shock-absorbing and energy-absorbing recyclable material are as follows: The mixture is added to a twin-screw extruder and melt-blended at 350-400 r / min, a feeding rate of 15-17 kg / h, a nitrogen atmosphere, and 150-160°C. The mixture is then pelletized to obtain a shock-absorbing and energy-absorbing recyclable material.

10. A shock-absorbing and energy-absorbing recyclable material, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.